Reward System Realizes Teacher Job Satisfaction at An-Nahl Integrated Islamic High School, Jambi City - Mardayanti, Arlen; Samsu, Samsu; Badarussyamsi, Badarussyamsi; Fuadi, Afif (Dinasti International Journal of Management Science, 2024)
This study aims to analyze in depth the "Reward System in Realizing Teacher Job Satisfaction at SMAIT An-Nahl Jambi City. This study is a study that uses a qualitative approach with data collection techniques using observation, interviews and documentation as supporting data. Data analysis techniques use qualitative techniques through domain analysis, taxonomy and components, and data is reduced, presented and concluded. The results of the study indicate that: 1) Forms of awards at SMA-IT An-Nahl are salary/honorarium, bonuses, umrah, gold, achievements, performance, praise and gratitude, career levels, leave, allowances and school institutional policies; 2) Forms of teacher job satisfaction at school include continuing to attend SMA-IT An-Nahl, enthusiasm in carrying out daily obligations, positive towards work, cooperation between leaders and subordinates, gratitude for God's blessings; 3) Awards are given at school every three months and once a year; 4) Driving and inhibiting factors in the reward system create teacher job satisfaction at SMA-IT An-Nahl such as incentives to increase teacher motivation. Inhibiting factors include suboptimal funding; and 5) The results achieved from the awards given to teachers are that teachers demonstrate good attitudes and behaviors in accordance with the demands and guidance of the school, teachers continue to teach at An-Nahl. Based on the results of the study, it can be concluded that apart from the awards given at school, teachers feel job satisfaction because they feel called within themselves to teach.